Null mutation in shaking-B eliminates electrical, but not chemical, synapses in the Drosophila giant fiber system: a structural study. - Blagburn, J.M.; Alexopoulos, H.; Davies, J.A.; Bacon, J.P. (Journal of Comparative Neurology, 1999)
Mutations in the Drosophila shaking-B gene perturb synaptic transmission and dye coupling in the giant fiber escape system. The GAL4 upstream activation sequence system was used to express a neuronal-synaptobrevin-green fluorescent protein (nsyb-GFP) construct in the giant fibers (GFs); nsyb-GFP was localized where the GFs contact the peripherally synapsing interneurons (PSIs) and the tergotrochanteral motorneurons (TTMns). Antibody to Shaking-B protein stained plaquelike structures in the same regions of the GFs, although not all plaques colocalized with nsyb-GFP. Electron microscopy showed that the GF-TTMn and GF-PSI contacts contained many chemical synaptic release sites. These sites were interposed with extensive regions of close membrane apposition (3.25 nm +/- 0.12 separation), with faint cross striations and a single-layered array of 41-nm vesicles on the GF side of the apposition. These contacts appeared similar to rectifying electrical synapses in the crayfish and were eliminated in shaking-B2 mutants. At mutant GF-TTMn and GF-PSI contacts, chemical synapses and small regions of close membrane apposition, more similar to vertebrate gap junctions, were not affected. Gap junctions with more vertebratelike separation of membranes (1.41 nm +/- 0.08) were abundant between peripheral perineurial glial processes; these were unaffected in the mutants.